The influence of the forest corridors to the north of the Andes on the diversification of the bright‐rumped Attila, Attila spadiceus (Passeriformes, Tyrannidae), during the climatic oscillations of the middle Pleistocene - Patrícia Mendonça; Lincoln Silva Carneiro; Victor Leandro‐Silva; Alexandre Aleixo; Juliana Araripe; Péricles S. Rêgo (Ecology and Evolution)
Abstract This study aims to enhance our understanding of the temporal and spatial processes scales governing the evolutionary diversification of Neotropical birds with Trans‐ and Cis‐Andean populations of the species Attila spadiceus from South and Central America. Through a multilocus analysis of the mitochondrial (CytB and ND2) and nuclear genes (I7BF, I5BF, and G3PDH) of 41 samples representing six subspecies, we describe the existing molecular lineages of A. spadiceus, and estimate their demographic dynamics. We used Ecological Niche Modeling (ENM) with six different algorithms to predict the potential distribution of A. spadiceus in both present‐day and past scenarios, examining the overlap climatic niche between Cis‐ and Trans‐Andean lineages. The analysis confirms a relatively recent divergence of the Trans‐ and Cis‐Andean lineages, at approximately 0.25 million years ago (Ma). The niche modeling supports the existence of a dynamic scenario of the expansion and retraction of forest corridors in northwestern South America during the last glaciation. This suggests that the earlier orogenesis of the Andes was not a primary determinant of this dichotomy. Additionally, the analysis of population dynamics indicated a trend of increasing population size starting at 0.05 Ma for both lineages. Our findings highlight the significance of Pleistocene Forest corridors north of the Andes as the key factor maintaining communication before the separation of the lineages, likely associated with the retraction of this forest. We highlight the absence of any significant differentiation between the disjunct Amazonian and Atlantic Forest populations, at both part of the Cis‐Andean lineage. The phylogeographic profile of A. spadiceus diverges from the patterns observed in other Neotropical birds, which emphasizes the need for further research on the role of the forest corridors of the northern Andes as drivers of diversification, to provide comprehensive insights into the processes that led to the formation of the region's present‐day avian diversity.